2007
DOI: 10.1111/j.1460-9568.2007.05966.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and transmitter‐specific pre‐ and postsynaptic changes in the rat cerebral cortex during ageing

Abstract: Recent studies suggest that age-related cognitive decline is correlated with an excitatory-inhibitory imbalance in synaptic discharges on pyramidal neurons. This study focuses on whether ageing and cognitive status correlates with relative numbers of excitatory and inhibitory presynaptic boutons. We investigated the density of excitatory and inhibitory presynaptic inputs across several areas of the rat cerebral cortex in young and aged male Fischer 344 rats. Aged animals were segregated into aged cognitively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 62 publications
5
28
0
Order By: Relevance
“…In the EPL, the ratio between symmetrical and asymmetrical synapses is also preserved, as well as the density of reciprocal synapses, supporting the hypothesis that D:D symmetrical and asymmetrical synapses are interdependent (31). Such balance between synapse types has also been reported in frontal and parietal cortices, where the ratio of excitatory to inhibitory synapses is maintained during the parallel decrease of both presynaptic boutons (34). However, maintenance of this balance is not a ubiquitous phenomenon, because inhibitory synapses are preferentially affected by the synapse reduction in the sensorimotor cortex (32).…”
Section: Discussionsupporting
confidence: 61%
“…In the EPL, the ratio between symmetrical and asymmetrical synapses is also preserved, as well as the density of reciprocal synapses, supporting the hypothesis that D:D symmetrical and asymmetrical synapses are interdependent (31). Such balance between synapse types has also been reported in frontal and parietal cortices, where the ratio of excitatory to inhibitory synapses is maintained during the parallel decrease of both presynaptic boutons (34). However, maintenance of this balance is not a ubiquitous phenomenon, because inhibitory synapses are preferentially affected by the synapse reduction in the sensorimotor cortex (32).…”
Section: Discussionsupporting
confidence: 61%
“…For the count of TrkAimmunoreactive (IR) varicosities, size and shape criteria were applied to separate varicosities from axons. Confocal settings for acquisition and quantification were as previously described (Majdi et al, 2007;Allard et al, 2011). Differences between groups (vehicle vs treated) were analyzed using Student's t tests.…”
Section: Confocal Microscopy and Quantificationmentioning
confidence: 99%
“…Therefore, cognitive decline could be a result of dysregulation of synaptic function and neurotransmission. Previous studies have reported age-related changes in glucose metabolism and long term potentiation as well as levels of neurotransmitters (dopamine, norepinephrine, 5-HT, GABA, acetylcholine) and trophic factors like brain-derived neurotrophic factor, nerve growth factor, insulin-like growth factor-1 (Baxter et al, 1999; Foster, 2007; Gant et al, 2006; Gavilan et al, 2007; Hwang et al, 2006; Majdi et al, 2007; Mora et al, 2007; Rowe et al, 2007; Shi et al, 2007; Smith et al, 2000). Structural changes in the aging brain have also been demonstrated such as atrophy of various aspects of dendritic and synaptic morphology and vascular rarefaction (Dickstein et al, 2007; Shi et al 200; Sonntag et al 1997, 2000).…”
Section: Introductionmentioning
confidence: 99%